Analysis of the Implementation of the Tabarru' Contract in Sharia Insurance Based on DSN-MUI Fatwa No. 53 of 2006 - Annisa Sativa; Akbar Chaniago; Zahra Chairawani Husni; Aisyah Sabrina Tanjung (ISNU Nine-Star Multidisciplinary Journal, 2025)
This study aims to analyze the implementation of the tabarru' contract in Islamic insurance in Indonesia by referring to the DSN-MUI Fatwa No. 53 of 2006. The tabarru' contract is a gift agreement that aims to provide mutual assistance between insurance participants, in accordance with sharia principles such as justice, solidarity, and transparency. This study uses a library method by analyzing literature related to fatwas, laws, and academic references. The results of the study indicate a gap between the theory and practice of the tabarru' contract, especially in the management of underwriting surpluses that allow for the return of funds to participants. However, the implementation of this contract has increased public trust in Islamic insurance through the separation of tabarru' funds from company operational funds, transparency of management, and collective responsibility among participants. This study emphasizes the importance of public education to improve understanding of the tabarru' contract as a sharia financial solution that supports shared prosperity. With better implementation, the tabarru' contract is expected to not only function to protect risks, but also reflect the values of worship and social service in Islam.